Performance and emission characteristics of diesel engine fueled with rice bran biodiesel and n-butanol - Geetesh Goga; Bhupendra Singh Chauhan; Sunil Kumar Mahla; Haeng Muk Cho (Energy Reports, 2019)
Due to the depletion of petroleum products and fatal emissions from the tailpipe of diesel engines it has become a need to seek for the alternative of petroleum products for long-term use. Currently, researchers and experts have come to the conclusion that biodiesel along with higher alcohols can be an appropriate substitute for this situation. Former investigations have presented that biodiesel and higher alcohol can help in improving the performance and depreciating harmful exhaust gases in a diesel engine. In the current investigation blends of diesel, rice bran biodiesel and n-butanol were prepared to check its effect on performance and emission characteristics of a diesel engine. Biodiesel was prepared by single stage alkaline transesterification process in this study and after that blends of diesel-biodiesel and diesel-biodiesel-n butanol were prepared as B10, B20, B10 nb10 and B20 nb20. Then these blends were tested in a single cylinder, small utility diesel engine with a rated power output of 3.73 kW to compare them with baseline diesel. Experimental investigation demonstrates that blends of rice bran biodiesel and n-butanol can be used as a fuel in a diesel engine without any change in the engine.
Keywords: 330; Biodiesel; Butanol; Diesel engine; Emission